Measure for measure - Shakespeare, William, 1564-1616.; Lever, J. W. (Julius Walter) (London : AS, 2001)
An annotated edition of Shakespeare's tragicomedy in which an unjust Viennese deputy offers to lift a death sentence from a young woman's brother in return for sexual favors from her; also includes essays on Shakespeare's theatrical world and his texts, and a scholarly introduction.
Includes bibliographical references.
Young Adult.
Young Adult
Keywords: Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616.; Brothers and sisters -- Drama; Chastity -- Drama; Chastity -- Drama; Comedies; Siblings -- Drama; Vienna (Austria) -- Drama; Vienna (Austria) -- Drama